Pedra de tropeço na vida do capital: ocupações, lutas e resistências dos movimentos de moradia na cidade de Goiânia/Goiás - Oliveira, Mirian Maria de (2025)
This thesis analyzes the trajectory of social movements in the struggle for land and housing in the city of Goiânia. The objective is to identify, analyze, and understand the trajectory and struggles of housing movements, focusing on the social movement - the State Union for Popular Housing of Goiás (UEMPGO). The study begins with the history of Goiânia (Goiás) from its foundation in 1933, a period marked by the first occupations, struggles, and resistances of the population without access to land. These struggles became more organized through housing movements starting in the 1980s, culminating in the creation of UEMPGO in 2003. Our hypothesis is that UEMPGO enabled access to the right to housing for families engaged in the social movement who would otherwise lack the means to obtain homeownership. We adopt a critical and dialectical perspective aimed at a socio-critical understanding of reality. The methodology employed is qualitative research, using oral history to facilitate attentive listening to the history of the social movement, and includes bibliographic, documental, and field research with participants who are leaders of some housing movements in Goiânia. The results indicate that Goiânia was not planned to accommodate the low-income population. Its construction prioritized wealth accumulation, alongside poverty concentration. The city was developed for capital through real estate speculation, resulting in socio-spatial segregation, gentrification, and a deepening of social inequality. Over the years, social housing policies have failed to meet the needs of this population. Amid such inequalities, the housing movement fights for the right to land and the construction of homes for lower-income classes, as well as for public policies